Prioritizing agricultural investments across commodities for income growth and poverty reduction: Methods and applications - Martin, Will; Minot, Nicholas (International Food Policy Research Institute, 2021)
Some agricultural investments are commodity-specific, meaning that they increase the productivity of production, processing, or marketing of a single agricultural commodity or a set of closely-related commodities. Examples include investment in cassava breeding, expanding cotton ginning capacity, irrigation for rice production, expansion of cold storage capacity for horticultural exports, or road investment to a region whose main product is maize. Traditional cost-benefit analysis estimates the effect of in-vestments on net income assuming that the investment is not large enough to influence market prices. However, a different approach is needed when the investment affects market prices and/or there is an interest in other outcomes such as poverty reduction. This report describes an approach to estimating the impact of commodity-specific agricultural investments on income, poverty, and other measures of welfare. This approach can be extended to identify the optimal allocation of an investment budget across commodities subject to a given objective function. For example, it could be used to allocate agricultural research funds across commodities to maximize income, poverty reduction, or a weighted average of the two.